A core outcome set for damage control laparotomy via modified Delphi method. Issue 1 (4th January 2022) - Byerly, Saskya; Nahmias, Jeffry; Stein, Deborah M; Haut, Elliott R; Smith, Jason W; Gelbard, Rondi; Ziesmann, Markus; Boltz, Melissa; Zarzaur, Ben L; Bala, Miklosh; Bernard, Andrew; Brakenridge, Scott; et al.
Abstract : Objectives: Damage control laparotomy (DCL) remains an important tool in the trauma surgeon's armamentarium. Inconsistency in reporting standards have hindered careful scrutiny of DCL outcomes. We sought to develop a core outcome set (COS) for DCL clinical studies to facilitate future pooling of data via meta-analysis and Bayesian statistics while minimizing reporting bias. Methods: A modified Delphi study was performed using DCL content experts identified through Eastern Association for the Surgery of Trauma (EAST) 'landmark' DCL papers and EAST ad hoc COS task force consensus. Results: Of 28 content experts identified, 20 (71%) participated in round 1, 20/20 (100%) in round 2, and 19/20 (95%) in round 3. Round 1 identified 36 potential COS. Round 2 achieved consensus on 10 core outcomes: mortality, 30-day mortality, fascial closure, days to fascial closure, abdominal complications, major complications requiring reoperation or unplanned re-exploration following closure, gastrointestinal anastomotic leak, secondary intra-abdominal sepsis (including anastomotic leak), enterocutaneous fistula, and 12-month functional outcome. Despite feedback provided between rounds, round 3 achieved no further consensus. Conclusions: Through an electronic survey-based consensus method, content experts agreed on a core outcome set for damage control laparotomy, which is recommended for future trials in DCL clinical research. Further work is necessary to delineate specific tools and methods for measuring specific outcomes. Level of evidence: V, criteria